2021
DOI: 10.1186/s12913-021-06843-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the treatable burden of severe aortic stenosis in Australia: current and future projections within an ageing population

Abstract: Background We aimed to address the paucity of information describing the treatable burden of disease associated with severe aortic stenosis (AS) within Australia’s ageing population. Methods A contemporary model of the population prevalence of symptomatic, severe AS and treatment pathways in Europe and North America was applied to the 2019 Australian population aged ≥ 55 years (7 million people) on an age-specific basis. Applying Australian-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(71 reference statements)
0
18
0
Order By: Relevance
“… 17 The same broad methods were also applied to an equivalent study of the treatable burden of AS in Australia. 7 The primary basis for this study (in respect to providing AS-specific data) was two meta-analyses of AS that systematically reviewed and analysed the relevant public health to clinical literature to build contemporary models of the likely burden and treatment of severe AS. 15 16 The most recent of these reports synthesised data from 9723 cases of severe AS from 7 studies (predominantly from North America and Europe/UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 The same broad methods were also applied to an equivalent study of the treatable burden of AS in Australia. 7 The primary basis for this study (in respect to providing AS-specific data) was two meta-analyses of AS that systematically reviewed and analysed the relevant public health to clinical literature to build contemporary models of the likely burden and treatment of severe AS. 15 16 The most recent of these reports synthesised data from 9723 cases of severe AS from 7 studies (predominantly from North America and Europe/UK).…”
Section: Methodsmentioning
confidence: 99%
“…A pragmatic approach to estimate the treatable burden of disease imposed by severe AS in the UK was applied using similar methods previously used to derive what proved to be an accurate forecast of the contemporary and projected burden of heart failure in the UK 17. The same broad methods were also applied to an equivalent study of the treatable burden of AS in Australia 7. The primary basis for this study (in respect to providing AS-specific data) was two meta-analyses of AS that systematically reviewed and analysed the relevant public health to clinical literature to build contemporary models of the likely burden and treatment of severe AS 15 16.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we demonstrated a high risk of short- and longer-term mortality associated with moderate AS that warrants further research to understand how to optimally monitor and, if necessary, intervene, in affected individuals. The urgency to apply a more nuanced and cost-effective approach to AS management will only increase as the number of individuals living with this deadly condition inevitably rises in many countries [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the causal mechanism, the high risk of mortality amongst those with moderate AS suggests the need for closer surveillance in this subgroup and referral to a Heart Valve Clinic when indicated: noting the resource implications for such management [ 14 ]. Furthermore, these results support a role for ongoing prospective trials in those with moderate AS to assess the role of AVR in mitigating the observed risk.…”
Section: Discussionmentioning
confidence: 99%